(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2019)
In this paper, I consider the relationship that obtains between disgust and the idea of a just society. Contra Martha C. Nussbaum, who argues that disgust poses dangers to a just society, I contend that disgust can either damage or promote the construction of a just society. In fact, I largely agree with Nussbaum’s perspective on disgust, except for this point: disgust, I think, is not necessarily dangerous for a just society, but can also be useful and constitute an important element for its development. In order to justify my claim, first, I will comment on Nussbaum’s criticism of disgust. Second, I will analyse Paul Rozin and April E. Fallon’s seminal study on disgust, which Nussbaum’s own research fully presupposes. Third, I will outline a slightly different, indeed “holistic” view on disgust, and bring forward some arguments for the use of disgust in order to construct a just society.